ChemInform Abstract: Efficient Copper‐Catalyzed Trifluoromethylation of Aromatic and Heteroaromatic Iodides: The Beneficial Anchoring Effect of Borates. Issue 7 (29th January 2015) - Gonda, Zsombor; Kovacs, Szabolcs; Weber, Csaba; Gati, Tamas; Meszaros, Attila; Kotschy, Andras; Novak, Zoltan
Abstract The novel method for the copper‐catalyzed trifluoromethylation of aromatic and heteroaromatic iodides uses silane (II) in the presence of trimethyl borate.